2013
DOI: 10.1111/jfs.12052
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Vegetative Cells and Spores of Bacillus cereus in Two Food Systems

Abstract: The survival and growth of vegetative cells and spores of toxigenic Bacillus cereus CFR 1534 was investigated in a dehydrated (dry mix) blend of flour (roasted finger millet and Bengal gram) and chocolate milk. In the case of dry mix, there was a marginal initial increase of 2 logs in 2 days of storage at 20 and 30C, respectively. In chocolate milk, there was an increase of 1 log with certain inoculum levels introduced and storage temperatures. The survival pattern of vegetative cells/spores was primarily infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Though some of the identified Bacillus spp. were reported to be human pathogens (Ehling-Schulz et al, 2019;Celandroni et al, 2016;Desai and Varadaraj, 2013), their counts were low and can therefore be considered to be at a safe level. Bacteria of the B. pumilus clade were not identified up to the species level using the MALDI-TOF MS analysis and partial 16S rDNA sequencing.…”
Section: Microbial Ecology In Pot-pollen Samplesmentioning
confidence: 99%
“…Though some of the identified Bacillus spp. were reported to be human pathogens (Ehling-Schulz et al, 2019;Celandroni et al, 2016;Desai and Varadaraj, 2013), their counts were low and can therefore be considered to be at a safe level. Bacteria of the B. pumilus clade were not identified up to the species level using the MALDI-TOF MS analysis and partial 16S rDNA sequencing.…”
Section: Microbial Ecology In Pot-pollen Samplesmentioning
confidence: 99%
“…Considering the public health significance of foodborne pathogenic bacterial species and the hazards that could be associated with their survival during storage of food products, in an earlier study by the authors (Desai and Varadaraj, 2013), it was reported that survival pattern of vegetative cells/spores of Bacillus cereus in two selected food products was primarily influenced by initial number of contamination and to a certain extent by the water activity of food matrices. In the present study, the focus was on a more serious pathogen, L. monocytogenes in milk-based foods, wherein the study included two very popular and more commonly consumed products, namely (i) ice cream and (ii) mango pulp-based lactic fermented milk.…”
Section: Introductionmentioning
confidence: 99%